2005
DOI: 10.1083/jcb.200501048
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular domains of FasL and Fas are sufficient for the formation of supramolecular FasL-Fas clusters of high stability

Abstract: Using fluorescent variants of Fas and FasL, we show that membrane FasL and Fas form supramolecular clusters that are of flexible shape, but nevertheless stable and persistent. Membrane FasL-induced Fas clusters were formed in caspase-8– or FADD-deficient cells or when a cytoplasmic deletion mutant of Fas was used suggesting that cluster formation is independent of the assembly of the cytoplasmic Fas signaling complex and downstream activated signaling pathways. In contrast, cross-linked soluble FasL failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
70
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 41 publications
(79 reference statements)
7
70
3
Order By: Relevance
“…Fas belongs to the tumor necrosis factor receptor (TNFR)-I type family. It has one extracellular domain rich in cysteins that binds FasL, and another cytoplasm domain involved in death signals (103). FasL is an inductive molecule expressed on T cells, and weighs 40 kDa.…”
Section: Fas-fasl Intercellular Linkage-mediated Pathwaymentioning
confidence: 99%
“…Fas belongs to the tumor necrosis factor receptor (TNFR)-I type family. It has one extracellular domain rich in cysteins that binds FasL, and another cytoplasm domain involved in death signals (103). FasL is an inductive molecule expressed on T cells, and weighs 40 kDa.…”
Section: Fas-fasl Intercellular Linkage-mediated Pathwaymentioning
confidence: 99%
“…Following trimerization of Fas after ligation with Fas-L, the receptor rapidly recruits procaspase-8 through the key adaptor protein called Fas-associated protein with death domain (FADD) (Chinnaiyan et al, 1995) that transmitts the death signal (Algeciras-Schimnich et al, 2002;Henkler et al, 2005). FADD protein carries a death domain (DD) at its C-terminal region, involved in the binding of Fas, which also displays a single serine phosphorylation site that is essential, inter alia, for cell cycle regulation and survival/proliferation in some cells (Scaffidi et al, 2000;Zhang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 At the molecular level, we and others already reported that the pro-death role of Fas palmitoylation relies on (i) the formation of supramolecular Fas aggregates 9 and (ii) Fas targeting in nanodomains enriched in cholesterol and glycosphingolipids, which is a prerequisite for proper activation of Fas-induced cell death. 8,[17][18][19][20][21] In these domains and upon FasL binding, palmitoylation allows Fas to recruit ezrin and actin cytoskeleton that lead to Fas internalization and transmission of death signal. 8 We thus aimed at understanding how Fas palmitoylation is regulated.…”
mentioning
confidence: 99%